Analisis Kritik Sastra Cerpen “ Senyum Karyamin “ Karya Ahmad Tohari Dengan Pendekatan Objektif - Sari Nurima br Lumban Batu (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the literary criticism found in Ahmad Tohari's short story